2015
DOI: 10.2134/jeq2015.02.0108
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Characterization and Contribution from Eroding Streambank Soils of Vermont's Lake Champlain Basin

Abstract: Streambank erosion is an important contributor to sediment and nutrient export. This study determined total P (TP), soil-test P (Modified Morgan's, MM-P), and the degree of P saturation (DPS) in eroding riparian soils along four Lake Champlain Basin stream corridors. We investigated the relationship between these data and soil texture and with a series of GIS-derived landscape metrics. We also quantified the potential P load from eroding streambanks using remote sensing. Soil samples were taken from 76 erosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
(59 reference statements)
2
35
0
Order By: Relevance
“…Land uses with higher TP concentrations in the interior had higher levels of TP in the streambank soils (Fig. 2a), although the streambank TP concentration for hay was below the 0‐ to 15‐cm riparian soil average found in nearby watersheds by Ishee et al (2015), and the corn streambank TP was only 13% higher than this average. We conclude that higher TP values of the streambank soils for agricultural sites relative to forest sites cannot unequivocally be assigned to the land use.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Land uses with higher TP concentrations in the interior had higher levels of TP in the streambank soils (Fig. 2a), although the streambank TP concentration for hay was below the 0‐ to 15‐cm riparian soil average found in nearby watersheds by Ishee et al (2015), and the corn streambank TP was only 13% higher than this average. We conclude that higher TP values of the streambank soils for agricultural sites relative to forest sites cannot unequivocally be assigned to the land use.…”
Section: Discussionmentioning
confidence: 90%
“…Studies of native levels of TP in northeastern US parent material and soils, including in riparian soils within Vermont, point to concentrations of 600 to 800 mg TP kg −1 in soils relatively low in organic matter (Yang et al, 2013; Ishee et al, 2015; Young and Ross, 2016). For this study, we used three SDs above the average determined nearby by Ishee et al (2015), or 1172 mg kg −1 , to define a local soil that was elevated in TP (assumed to be derived from land management [manure or fertilizer additions]). The agricultural interior sites in our study appear to have legacy P that has nearly doubled the TP status (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young et al (2012) also reported a wide range in riparian soil TP with low MM‐P. Ishee et al (2015) showed that central Vermont riparian sites had low average MM‐P and relatively low P saturation levels (estimated by the molar ratio of acid ammonium oxalate–extractable P to the sum of oxalate‐extractable Al and Fe) in surface and subsurface soils. Because MM‐P concentration is a good index of plant availability and is well correlated with extracts designed to estimate potential P release to runoff (Magdoff et al, 1999), orthophosphate release potential would also presumably be low, assuming aerobic soil conditions are maintained (Young and Ross, 2001; Young and Briggs, 2008).…”
Section: Resultsmentioning
confidence: 95%
“…Because MM‐P concentration is a good index of plant availability and is well correlated with extracts designed to estimate potential P release to runoff (Magdoff et al, 1999), orthophosphate release potential would also presumably be low, assuming aerobic soil conditions are maintained (Young and Ross, 2001; Young and Briggs, 2008). Based on low MM‐P‐Color and P sorption saturation, Ishee et al (2015) suggested eroded riparian stream bank soils could function as a net sink for phosphate in the watershed. Given that there are other sources of P in the Rock River watershed more enriched with P relative to the TP and MM‐P concentrations of the soils in the present study (e.g., P in overland runoff flows from crop fields), eroded stream bank soils would be expected to be a minor contributor of bioavailable P to the river based on their low MM‐P status.…”
Section: Resultsmentioning
confidence: 99%